Penerapan Model Make A Match untuk Meningkatkan Hasil Belajar Siswa Materi Makna Simbol dan Sila Pancasila Kelas IV SDN 129 Hutarimbaru Panyabungan Timur - Nida Aisyah; Rahmi Seri Hanida; Ali Yusron (CV. PUSDIKRA MITRA JAYA, 2026)
This study aims to assess how the Make a Match learning model can enhance students’ learning outcomes in the subject of social issues among Grade IV students at SD Negeri 129 Hutarimbaru Panyabungan Timur. This research employs Classroom Action Research (CAR), conducted over two cycles. Each cycle includes four stages: planning, implementation, observation, and reflection. The study subjects comprised 21 students, with 9 males and 11 females from Grade IV at SD Negeri 129 Hutarimbaru Panyabungan Timur for the academic year 2024/2025. Data collection methods included observation sheets and tests. The data were analyzed both descriptively and quantitatively, with validity and reliability tests conducted to support the findings.The results indicate that the application of the Make a Match learning model significantly improved students’ learning outcomes by meeting the Minimum Mastery Criteria (KKTP). The improvement is evident across each cycle: in the pre-cycle, the students’ average score was 52.4, with a pass percentage of 47.6%. After the first cycle, the average score rose to 73.4, with a passing percentage of 61.9%. In the second cycle, the average score increased to 82.6, achieving a 100% passing rate. Based on these findings, it can be concluded that students’ learning outcomes improved significantly following the implementation of the Make a Match learning model.